Study of aluminum nitride precipitation in Fe- 3%Si steel - F.L. Alcântara; R. Barbosa; M.A. Cunha (Materials Research, 2013)
For good performance of electrical steels it is necessary a high magnetic induction and a low power loss when submitted to cyclic magnetization. A fine dispersion of precipitates is a key requirement in the manufacturing process of Fe- 3%Si grain oriented electrical steel. In the production of high permeability grain oriented steel precipitate particles of copper and manganese sulphides and aluminium nitride delay normal grain growth during primary recrystallization, causing preferential growth of grains with Goss orientation during secondary recrystallization. The sulphides precipitate during the hot rolling process. The aluminium nitride particles are formed during hot rolling and the hot band annealing process. In this work AlN precipitation during hot deformation of a high permeability grain oriented 3%Si steel is examined. In the study, transfer bar samples were submitted to controlled heating, compression and cooling treatments in order to simulate a reversible hot rolling finishing. The samples were analyzed using the transmission electron microscope (TEM) in order to identify the precipitates and characterize size distribution. Precipitate extraction by dissolution method and analyses by inductively coupled plasma optical emission spectrometry (ICP-OES) were used to quantify the precipitation. The results allowed to describe the precipitation kinetics by a precipitation-time-temperature (PTT) diagram for AlN formation during hot rolling.